EMPLOYMENT ENGAGEMENT AS A VARIABLE AFFECTING THE PERFORMANCE OF MICRO FINANCIAL INSTITUTION EMPLOYEES IN THE BOJONEGORO DISTRICT - Septian Yogi Aryanto; Sopiah Sopiah (International Journal of Economy, Education and Entrepreneurship, 2022)
People are the most valuable asset in service organizations to compete with other organizations. Organizational performance is reflected in the performance of its employees. Many factors, such as the relationship quality between leaders and employees, corporate support perceived by employees, and work engagement, affect organizational performance. This study examines the direct or indirect effect of leader-member exchange (LMX) and perceived administrative support (POS) on employee performance mediated by work engagement and conducted this research on employees of microfinance institutions in the Bojonegoro district. The sample of this study amounted to 192 employees from a total population of 366 employees obtained by proportional random sampling technique. Analysis of the data used is path analysis. The results of this study indicate that the direct effect of the results is significantly positive, except for the impact of POS on employee performance (hypothesis 4 is rejected). And work engagement has been proven to be a mediator variable in the relationship between LMX and POS on employee performance